Public Service Performance in Gianyar during the Covid-19 Pandemic: Time and Handling of Complaints Needs Special Attention - Richard Togaranta Ginting; Ni Made Ras Amanda Gelgel; Kadek Dwita Apriani (Universitas Pancasakti Tegal, 2022)
This study aims to determine the development trend of community satisfaction with the performance of the Gianyar Regency government, especially health services and social welfare services in the Covid-19 pandemic. This research is a survey research conducted to the Gianyar community regarding the Community Satisfaction Index on the performance of the Gianyar Regency government. This research uses measuring tools and indicators of the Regulation of the Minister of Administrative and Bureaucratic Reform Number 14 of 2017 concerning Guidelines for the Survey of Community Satisfaction on Public Service Delivery. The results showed that the indicators of time and complaint handling showed a low trend compared to other elements. The time indicator shows a score of 3.015 and the complaint handling indicator shows a score of 3.04. In general, the Community Satisfaction Index on Government Performance is good with an average score of 78.29.